2022
DOI: 10.1038/s41467-022-31923-y
|View full text |Cite
|
Sign up to set email alerts
|

Repeating fast radio burst 20201124A originates from a magnetar/Be star binary

Abstract: Fast radio bursts (FRBs) are cosmic sources emitting millisecond-duration radio bursts. Although several hundreds FRBs have been discovered, their physical nature and central engine remain unclear. The variations of Faraday rotation measure and dispersion measure, due to local environment, are crucial clues to understanding their physical nature. The recent observations on the rotation measure of FRB 20201124A show a significant variation on a day time scale. Intriguingly, the oscillation of rotation measure s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
43
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 44 publications
(46 citation statements)
references
References 97 publications
2
43
1
Order By: Relevance
“…A similar RM evolution has been found through the periastron passage of PSR B1259 −63/LS 2883 (e.g., Johnston et al 1996Johnston et al , 2005. Wang et al (2022a) proposed that FRB 20201124A and FRB 20190520B may reside in a magnetar/Be star binary system. The fastrotating Be star will form a decretion disk.…”
Section: Introductionsupporting
confidence: 68%
See 3 more Smart Citations
“…A similar RM evolution has been found through the periastron passage of PSR B1259 −63/LS 2883 (e.g., Johnston et al 1996Johnston et al , 2005. Wang et al (2022a) proposed that FRB 20201124A and FRB 20190520B may reside in a magnetar/Be star binary system. The fastrotating Be star will form a decretion disk.…”
Section: Introductionsupporting
confidence: 68%
“…Second, similar RM variations and reversals of repeating FRBs have been observed both in repeating FRBs (Anna-Thomas et al 2022;Dai et al 2022;Xu et al 2022) and in a binary system containing a pulsar and a massive Be star (PSR B1259−63/LS 2883; Johnston et al 1996Johnston et al , 2005. Wang et al (2022a) found that RM variations and reversals can be well understood in a magnetar/Be star binary system. Third, short-time RM variations have been measured in the pulsar binary system PSR B1744−24A (Li et al 2022).…”
Section: Introductionsupporting
confidence: 58%
See 2 more Smart Citations
“…The detection of microstructure in bursts from FRB 20200120E (Majid et al 2021;Nimmo et al 2022), together with its association with a globular cluster of M81 (Kirsten et al 2022), suggest an origin in a recycled pulsar system. Despite its origin in an inter-arm region of its late-type host galaxy (Xu et al 2022), FRB 20201124A illuminates extreme variability of its sub-AU magneto-ionic environment, suggestive of a magnetar/Be-star binary (Wang et al 2022). Such observational diversity among the small sample of just eight localized sources motivates the characterization of a larger sample of host galaxies and environments of repeating FRBs.…”
Section: Introductionmentioning
confidence: 99%